The role of adult facilitators in arts‐based extracurricular settings: Perceived factors for success of adult–youth relationships. Issue 1 (22nd January 2021) - Chapin, Laurie A.; Fowler, Michelle A.; Deans, Carolyn L.
Abstract: Extracurricular arts programmes and supportive adult relationships provide youth with opportunities for positive development, however, more research about how relationships within these programmes develop and what factors and practices adults use to guide their work would help to improve youth programmes' outcomes. Eight Film Club facilitators at an after‐school film‐making club for students in grades 5 through 8 were interviewed about their perceived their role and what practices they successfully utilised. The semistructured interviews were then thematically analysed. Facilitators perceived the development of authentic and supportive relationships provided a foundation for meaningful learning. Rather than being directive, the facilitators had a collaborative approach to engagement, which allowed for social and emotional learning opportunities and established youth agency. Relationships within creative extracurricular spaces, which are youth‐led and include supportive adult facilitators may provide young people with valuable opportunities for social, emotional and identity development.